Optimalisasi Pengelolaan Keuangan pada UMKM Kerupuk Jagung melalui Peningkatan Pengetahuan Akuntansi - Aranta Prista Dilasari; Viky Indarto; Muhammad David; Ainul Afif; Mirzalia Imala Dewi (Pusat Riset dan Inovasi Nasional, 2022)
This activity aims to help Koko Nino Corn Crackers MSMEs manage their finances better, such as determining the right selling price, making production budget plans, sales reports, and calculating profits earned. This will help their business units develop their capital to a greater extent. Apart from that, this activity also aims to improve product packaging and expand the marketing reach of the product. The methods used in this activity include observation, material presentation, and training practices regarding determining selling prices, making production budget plans, sales reports, calculating profits, appropriate packaging, and evaluation. The goals that Koko Nino Corn Crackers wants to achieve through this activity are increasing sales, the ability to make daily financial records, simple financial reports, determine more accurate selling prices, change more attractive packaging with various sizes, and expand the product's marketing they reach.